Progressive habituation to separation alleviates the negative effects of weaning in the mother and foal. (November 2018) - Lansade, Léa; Foury, Aline; Reigner, Fabrice; Vidament, Marianne; Guettier, Elodie; Bouvet, Gwenaelle; Soulet, Delphine; Parias, Céline; Ruet, Alice; Mach, Nuria; Lévy, Frédéric; Moisan, Marie-Pierre
Highlights: Early and definitive separation of an offspring from its mother is detrimental. These negative effects can be alleviated by progressive habituation to separation. Progressive habituation reduced stress to the mothers and their foals. It also favored a less fearful and more curious personality in foals. Expression of 22 genes discriminated the foals based on the weaning method. Abstract: Early and definitive separation between offspring and their mothers has negative consequences on behavioral and physiological responses. This study compared sudden and definitive weaning (Sudd group, N = 16) and weaning involving progressive habituation to separation using a fence line during the month preceding definitive separation (Prog group, N = 18). The impact of these two methods was assessed in both foals and their mothers through behavioral and biological parameters, including salivary cortisol, telomere length and blood transcriptomes. On the day of definitive separation, Prog foals neighed and trotted less and presented lower cortisol levels than Sudd foals. The weaning type also acted on the foals' personality development; Prog foals became more curious, less fearful and less gregarious than Sudd foals, and the effects remained visible for at least 3 months. In principal component analysis, the Sudd and Prog groups were well separated along a factor where fear, reactivity and gregariousness correlated with high cortisol levels, but curiosity was associated with an increased telomere length and higher expression of genes involved in mitochondrial functions. Progressive weaning was also beneficial in mares. Principal component analysis showed that most Sudd group mares had higher cortisol levels and displayed more alert postures, neighs and activity on the day of weaning, indicating higher stress levels, while Prog mares had profiles that were characterized by more time spent resting on the day of weaning and longer telomere lengths. In conclusion, this study shows that progressive habituation to separation alleviates the negative effect of definitive weaning on both the mother and her young compared to sudden separation.